Pengaruh Pemberian GA3 terhadap Perkecambahan Embrio Somatik Kakao - Cici Tresniawati; Nur Ajijah; Deden Sukmajaya; Dewi Sukma (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Germination process of somatic embryos is one of critical steps in somatic embryogenesis. The conversion of somatic embryos into plantlets is still low and adding kinetin, ABA, NAA, and GA3 to the germination medium of cacao somatic embryos may increase it. The study aimed to investigate the effect of GA3 on somatic embryo germination at the cotyledonary phase. The study was conducted in the Indonesian Industrial and Beverage Crops Research Institute (IIBCRI) Tissue Culture Laboratory from May to November 2017. The study used a factorial completely randomized design (CRD) with seven replications. The first factor was the cacao genotypes, namely SCA 6 and MCC 02, and the second factor was four concentrations of GA3, namely 0.0; 1.0; 3.0; and 5.0 mg/l. Characters observed were the percentage of shooting cotyledonary embryos, the percentage of rooting cotyledonary embryos, the percentage of shooting and rooting cotyledonary embryos, percentage of browning cotyledonary embryos, root length, shoot length, and hypocotyl length at one and two months old. The results showed no interaction between genotypes and GA3 concentrations on all observed characters. Adding GA3 at 1,0 mg/l concentration tends to increase the percentage of shooting cotyledonary embryos of SCA 6 and rooting cotyledonary embryos of MCC 02. SCA 6 clone has a higher percentage of shooting cotyledone, shooting and rooting cotyledone, and browning cotyledone compared to those of MCC 02.